VOCATIONAL EDUCATION FOR SUSTAINABLE DEVELOPMENT: FOREIGN EXPERIENCE (Innovative professional education, 2024)
The impact of sustainable development on professional education in Germany has been studied. In vocational education and advanced training (Weiterbildung), sustainable development means awareness and responsibility for social justice and environmental protection, taking into account the company's economic interests. In order to realize this goal, certain tools are being implemented in vocational education in Germany – BBNE pilot projects and competence oriented towards sustainable development – which help to structurally fix sustainable development in the field of vocational  education.
Keywords: sustainable development, education for sustainable development, professional education, Germany, Ukraine